Retina‐Inspired Structurally Tunable Synaptic Perovskite Nanocones (Adv. Funct. Mater. 52/2021). (22nd December 2021) - Lee, Kyuho; Han, Hyowon; Kim, Youngwoo; Park, Jumi; Jang, Seonghoon; Lee, Hyeokjung; Lee, Seung Won; Kim, HoYeon; Kim, Yeeun; Kim, Taebin; Kim, Dongho; Wang, Gunuk; et al.
Abstract : Artificial Retinas In article number 2105596, Cheolmin Park and co‐workers demonstrate artificially intelligent photonic synapses by utilizing position‐dependent density tunable photoreceptive perovskite nanoscale cones templated in a self‐assembled block copolymer nanostructure. The synapses emulate the human retina with the spatial distribution of cones, and they recognize various visual information with a high degree of accuracy.